The Impact of Glutamatergic Synapse Dysfunction in the Corticothalamocortical Network on Absence Seizure Generation - Leitch, Beulah (Frontiers in Molecular Neuroscience, 2022)
Childhood absence epilepsy (CAE) is the most common paediatric epilepsy affecting 10–17% of all children with epilepsy. It is genetic in origin and the result of dysfunction within the corticothalamocortical (CTC) circuitry. Network dysfunction may arise from multifactorial mechanisms in patients from different genetic backgrounds and thus account for the variability in patient response to currently available anti-epileptic drugs; 30% of children with absence seizures are pharmaco-resistant. This review considers the impact of deficits in AMPA receptor-mediated excitation of (FFI) in the CTC, on absence seizure generation. AMPA receptors are glutamate activated ion channels and are responsible for most of the fast excitatory synaptic transmission throughout the CNS. In the stargazer mouse model of absence epilepsy, the genetic mutation is in stargazin, a transmembrane AMPA receptor trafficking protein (TARP). This leads to a defect in AMPA receptor insertion into synapses in parvalbumin-containing (PV+) inhibitory interneurons in the somatosensory cortex and thalamus. Mutation in the Gria4 gene, which encodes for the AMPA receptor subunit GluA4, the predominant AMPA receptor subunit in cortical and thalamic PV+ interneurons, also leads to absence seizures. This review explores the impact of glutamatergic synapse dysfunction in the CTC network on absence seizure generation. It also discusses the cellular and molecular mechanisms involved in the pathogenesis of childhood absence epilepsy.